Quality Management in the Faculty of Business Sciences at the José Faustino Sánchez Carrión National University: A Study Based on the Neutrosophic Linguistic 2-Tuple Model - Carlos Máximo Gonzales-Añorga; Julia Cecilia Yon-Delgado; Medalit Nieves Salcedo-Rodríguez; Mónica Rosario Yon-Delgado; Tito Edinson Quispe-Campos; Daniel Alberto Oswaldo Valenzuela-Narváez; Timoteo Solano-Armas; Viviana Inés Vellón Flores (Neutrosophic Sets and Systems)
This research study is the product of a comprehensive, profound, and objective diagnosis of the academic and administrative situation of the Faculty of Administrative Sciences and Tourism of the José Faustino Sánchez Carrión National University in Peru, which has allowed us to examine its management, the degree of efficiency, quality of training of academic schools and the factors that influence the quality of management. Quality in higher education is an important aspect to measure to guarantee the best results for our graduates in their professional lives within society. This paper aims to measure the quality of education in the aforementioned faculty, where the expected outcome is compared with the measured in reality, through a group of interviews. To facilitate assessment, a linguistic scale is used. On the other hand, the use of a triad of truthfulness, indeterminacy, and falseness allows us to deal explicitly with indeterminacy. That is why, for the processing of the collected data, we used the neutrosophic 2-tuple linguistic model.